Teori Generatif Transformatif Noam Chomsky : Analisis Dalam Hadis Nabi Tentang Niat - Fabrori, Fahri Muhaimin (Al-Bayan: Journal of Hadith Studies, 2023)
Hadith is a source of authority that belongs to Islam after the Koran. The Prophet Muhammad saw conveyed to his friends either by words, deeds, or predictions. With so many searched for or captured by the Companions of the Hadith, it will provide a different understanding and transmission. But still in the intent and purpose of the same. This study aims to analyze the Prophet's Hadith about intentions by using Noam Chomsky's transformative generative theory. In this article, the author presents two Hadiths about the intentions directed by Imam Bukhari, all with almost the same editorial. However, if you pay close attention, several Hadith sentences are not the same, whether in the form of addition/ziyadah, al-ittisa'/expansion, or alIhlal/replacement. The results of this study indicate that the Hadith about intention at number one shows that a hadith is a form of information that is convincing and general. Because two traditions of taukid have real meaning and several editorials that do not refer to special editorials. Meanwhile, Hadith number 52 does not contain taukid customs, which only shows information or cover. Then there is the addition of the sentence ila Allahi wa Rasulih which shows a more complete specificity and editorial.